When do Autocrats Create Sovereign Wealth Funds?. (June 2023) - Eldredge, Cody D.; Fails, Matthew D.
The recent proliferation of Sovereign Wealth Funds (SWFs) in authoritarian regimes is puzzling. While SWFs can generate political, financial, and geopolitical benefits in the long-term, their creation also sharply impedes an autocrat's ability to fund current patronage and other regime-stabilizing public and private goods. What explains the creation of autocratic SWFs? We argue that sovereign wealth funds are more likely to emerge when autocratic leaders possess a high degree of policy-making autonomy. Policy-making autonomy allows leaders to override any opposition from regime insiders who might prefer to keep capital at home and available for patronage. At the same time, such leaders are more politically secure, and thus are more confident that they will remain in power to reap the medium to long-term financial rewards of these funds. We operationalize this concept with indicators that measure whether an autocrat has consolidated their authority over the regime's party infrastructure and employ survival analysis on a global sample of autocratic regimes from 1960–2010. We find robust support for our argument and describe how our findings provide new insights on the political determinants of sovereign wealth funds and the consequences of authoritarian power-sharing institutions.